2011
DOI: 10.2478/v10181-011-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Density of tumor-associated macrophages (TAMs) and expression of their growth factor receptor MCSF-R and CD14 in canine mammary adenocarcinomas of various grade of malignancy and metastasis

Abstract: Several years ago, the presence of macrophages in the tumor microenvironment was thought to be an inflammatory response to kill the cancer cells. Now, this is clear that the inflammatory cells that exit blood vessels and migrate to the tumor tissue play an important role in cancer progression. Various cells present in the tumor microenvironment enhance cancer growth and invasiveness by secretion of tumor-enhancing products. That is why tumors should not be treated as only aggregates of cancer cells but as sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 13 publications
5
29
1
1
Order By: Relevance
“…Contrary to this study, another group showed that the relative percentage of CD4 + T-cells was higher in canine mammary tumors that metastasized, whereas CD8 + T-cells percentage was higher in tumors that did not metastasize [65, 66]. In terms of TAMs, their density was significantly higher in canine mammary adenocarcinomas that metastasized [64]. Furthermore, a microarray analysis to determine the global gene expression of a coculture of canine macrophages and canine mammary cancer cells showed an upregulation of genes involved in angiogenesis in TAMs and an increase in the migratory and invasive capabilities of cancer cells [95].…”
Section: Inflammatory Cells Tissue Invasion and Metastasismentioning
confidence: 72%
See 1 more Smart Citation
“…Contrary to this study, another group showed that the relative percentage of CD4 + T-cells was higher in canine mammary tumors that metastasized, whereas CD8 + T-cells percentage was higher in tumors that did not metastasize [65, 66]. In terms of TAMs, their density was significantly higher in canine mammary adenocarcinomas that metastasized [64]. Furthermore, a microarray analysis to determine the global gene expression of a coculture of canine macrophages and canine mammary cancer cells showed an upregulation of genes involved in angiogenesis in TAMs and an increase in the migratory and invasive capabilities of cancer cells [95].…”
Section: Inflammatory Cells Tissue Invasion and Metastasismentioning
confidence: 72%
“…There are few studies in canine mammary cancer regarding the influence of immune cells in tumor invasion and metastasis [55, 64, 95]. The role of lymphocytes and macrophages in canine mammary tumor metastasis is not fully understood.…”
Section: Inflammatory Cells Tissue Invasion and Metastasismentioning
confidence: 99%
“…For example, co-expression of CSF-1 and its receptor can be found in 50% of late stage breast and 70% of endometrial cancers [50,51]. During the course of our previous studies we found the CSF-1R expression in canine mammary cancer cells (Figure 10), as well as in tumour-associated macrophages [52]. The results of the studies of Kirma et al [53] suggest that the CSFs might have an autocrine role through CSF1R in epithelial tumour cells promoting their invasiveness into the surrounding matrix [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…U myszy zahamowanie ufosforylowanej formy STAT3 (p-STAT3) zmniejszyło liczbę mieloidalnych komórek supresoworych w guzie. U psów z nowotworem gruczołu sutkowego została wykazana bezpośrednia zależność pomiędzy liczbą mieloidalnych komórek supresorowych, ekspresją p-STAT3 a predyspozycją komórek nowotworowych do przerzutowania (18,29). W przerzutujących guzach gruczołu sutkowego suk liczba mieloidalnych komórek supresorowych i ekspresja p-STAT3 istotnie ze sobą korelują.…”
Section: Artykuł Przeglądowy Reviewunclassified